The History of Articulators: A Critical History of Articulators Based on ÃƒÂ¢Ã¢â€šÂ¬Ã…â€œGeometricÃƒÂ¢Ã¢â€šÂ¬Ã‚Â Theories of Mandibular Movement. Part IV: Needles, Wadsworth, and a Look at Some Who Followed - Edgar N. Starcke, DDS (Journal of Prosthodontics, 2003)
AS WAS discussed in Part III of this series, John Needles was an early and enthusiastic proponent of the Monson ÃƒÂ¢Ã¢â€šÂ¬Ã…â€œsphericalÃƒÂ¢Ã¢â€šÂ¬Ã‚Â theory